Pusat Pelatihan Selam di Kabupaten Kepulauan Selayar - Maghfirayanti, Nur; Lukman, Muhammad Yusri; said, Juhana (Universitas Muslim Indonesia, 2025)
One of the marine tourism trends that is starting to develop in Indonesia is diving tourism, which known as